2014
DOI: 10.1039/c4ta00437j
|View full text |Cite
|
Sign up to set email alerts
|

The general synthesis of Ag nanoparticles anchored on silver vanadium oxides: towards high performance cathodes for lithium-ion batteries

Abstract: A general approach has been developed to synthesize a series of silver vanadium oxides (SVOs) anchored with Ag nanoparticles (including AgVO3, Ag2V4O11, Ag0.33V2O5 and Ag1.2V3O8), which exhibit highly improved electrochemical performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…As important cathode candidates in LIBs, vanadium oxides and vanadate have attracted extensive interests owing to their abundant reservation, high specific capacity, and high Li + diffusion efficiency (Maingot et al, 1993; Torardi and Miao, 2002; Ng et al, 2007; Liu et al, 2009; Mai et al, 2010a,b; Wee et al, 2010; Liu and Yang, 2011; Pan et al, 2011a; Rui et al, 2011; Varadaraajan et al, 2011; Wang et al, 2011; Liang et al, 2013b; Jian et al, 2014; Zhou et al, 2014; Meng et al, 2016; An et al, 2017). For example, vanadium pentoxide (V 2 O 5 ) has a high theoretical capacity of 442 mA h g −1 , but its commercialization is still limited by poor cyclic stability (Owens et al, 1999; Cao et al, 2005; Wang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As important cathode candidates in LIBs, vanadium oxides and vanadate have attracted extensive interests owing to their abundant reservation, high specific capacity, and high Li + diffusion efficiency (Maingot et al, 1993; Torardi and Miao, 2002; Ng et al, 2007; Liu et al, 2009; Mai et al, 2010a,b; Wee et al, 2010; Liu and Yang, 2011; Pan et al, 2011a; Rui et al, 2011; Varadaraajan et al, 2011; Wang et al, 2011; Liang et al, 2013b; Jian et al, 2014; Zhou et al, 2014; Meng et al, 2016; An et al, 2017). For example, vanadium pentoxide (V 2 O 5 ) has a high theoretical capacity of 442 mA h g −1 , but its commercialization is still limited by poor cyclic stability (Owens et al, 1999; Cao et al, 2005; Wang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that the incorporation of metal cations (such as Li + , Na + , K + , Ag + , Zn 2+ , Cu 2+ , etc.) (Ma et al, 2008; Liu and Tang, 2009; Cheng and Chen, 2011; Liang et al, 2013a, 2014; Bach et al, 2014; Yang et al, 2016) into V 2 O 5 interlayers is favorable to improve the electronic conductivity (Zhou et al, 2014), simultaneously creating more Li + intercalation channels (Khoo et al, 2010) and improve the structural stability (Pan et al, 2011b). It was reported that introduction of K + into vanadium oxygen layers is effective to deliver high specific capacity and excellent reversibility by the pillar effect and larger interlamellar space (Baddour-Hadjean et al, 2011, 2014; Xu et al, 2012, 2015; Fang et al, 2015, 2016; Meng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A facile, general and scalable strategy to prepare Ag nanoparticles anchored on silver vanadium oxides (SVOs), including AgVO 3 , Ag 2 V 4 O 11 , Ag 0.33 V 2 O 5 and Ag 1.2 V 3 O 8 ,was developed . The preparation included the addition of NH 4 VO 3 powder to a solution of H 2 O 2 in deionized water, and after reaction, the authors observed the formation of a bright‐yellow solution.…”
Section: Synthesismentioning
confidence: 99%
“…The as‐obtained Ag/SVO hybrids demonstrated highly improved electrochemical properties because of the enhanced electron conductivity. For example, the Ag/AgVO 3 hybrid exhibited excellent rate capability: a high specific discharge capacity of 199 mA h g −1 can be reached at an ultra‐high discharge current density of 5 A g −1 …”
Section: Synthesismentioning
confidence: 99%
“…Recent studies imply that doping metal cations into V 2 O 5 layers is conducive to stable the whole structure [14], create more intercalation sites [15], or improve the intrinsic conductivity [16]. Considering these advantages, vanadate cathode materials have been intensively studied in the past few years [17e21].…”
Section: Introductionmentioning
confidence: 99%